PELAKSANAAN PENDIDIKAN AGAMA ISLAM PADA SEKOLAH DASAR NEGERI 2 LABUNGANAK KABUPATEN HULU SUNGAI TENGAH - Hatmiah Hatmiah (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The background of this research is the efforts of PAI teachers to increase students' interest in reading the Qur'an at MTs Shalatiyah Bitin with the formulation of the problem of how the efforts of PAI teachers to increase students' interest in reading the Qur'an at MTs Shalatiyah Bitin. The purpose of this study was to find out the efforts of PAI teachers in increasing students' interest in reading the Qur'an at MTs Shalatiyah Bitin. The subject of this research is the PAI teachers at MTs Shalatiyah Bitin. The object of this study is the efforts of PAI teachers to increase students' interest in reading the Qur'an at MTs Shalatiyah Bitin. Data collection techniques were carried out by means of interviews, observation and documentaries. Data processing techniques use data reduction, data display and data verification. Data were analyzed using descriptive qualitative. The results of this study can be concluded that the efforts of PAI teachers in increasing students' interest in reading the Qur'an at MTs Shalatiyah Bitin has been quite implemented, including: 1. The PAI teachers approach in increasing interest in reading the Qur'an in students at MTs Shalatiyah Bitin is good, because the PAI teachers at MTs. Shalatiyah Bitin has taken an individual approach and also made a motivational/motivated approach to students. Methods of PAI teachers in increasing interest in reading the Qur'an in students at MTs Shalatiyah Bitin, namely by using habituation methods and exemplary methods. 3. Obstacles faced by teachers towards students who are not very interested in reading the Qur'an can be overcome.